Student Admission Strategy In Increasing The Quality of Students - Febria Widodo, Firdaos; Rofiq, Ainur; Aprilianto, Andika (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2022)
The Madrasah Ibtidaiyah Al Ersyad City of Kediri is one of the madrasas that seeks to create future generations of Muslims who are good and worthy of pride for religion, nation and state, especially in the city of Kediri. MI Al Ersyad is under the auspices of an Islamic foundation with the characteristics of the Ahlussunnah waljamaah (Aswaja) ideology. And make a real contribution in society in the educational aspect by preparing a generation of students who are ready to face the challenges of the times. Against the background of the community's social environment, the foundation has succeeded in supporting the establishment of formal institutions starting at the PIAUD, Elementary and Secondary levels, therefore many strategies are carried out in the student acceptance process (PPDB) in each new school year. The formulation of the problems in this study are, 1) What are the student admission strategies in improving the quality of students at MI Al Ersyad, Kediri City?, 2) What are the supporting and inhibiting factors for student acceptance at MI Al Ersyad, Kediri City?. This study uses a qualitative approach to the type of case study research. Data collection techniques through observation, interviews, documentation, and triangulation. The results of this study are that the New Student Acceptance Strategy (PPDB) at MI Al Irsyad, Kediri City Islamic Boarding School District is a process that is carried out every new school year. This was done by managing the acceptance of new PPDB students at MI Al Ersyad, Kediri City in improving the quality of students, such as improving the strategic management of the formulation stage which was strengthened by the implementation stage through registration of two batches from 04 January to 31 March 2022, by selecting approximately 115 people. new students, up to the evaluation stages of New Student Admissions by measuring the quantity and quality of new students based on student test scores.